Desenvolvimento de um sistema de posicionamento interno baseado na potência do sinal de resposta de um sistema RFID - Murofushi, Rodrigo Hiroshi (2016)
Indoor positioning systems (IPS) locate objects in indoors environment, such as buildings, factories and warehouses. It is possible to design such system using several technologies, among which we can mention, ultrasound, wireless networks, infrared, among others. This dissertation presents an IPS based on RFID technology integrated to a selector bench. First, it was developed an IPS for a barrier-free environment in order to have a better understanding about the RFID technology and subsequently an IPS was designed for a practical study case. The estimated distance between an antenna and an electronic tag is calculated using the received signal strength indication (RSSI) from the tag. The method used depends on prior calibration and experiments conducted to validate and evaluate the system performance. The IPS designed to an environment without obstacles showed an absolute error of 5.9 cm considering the distance of 20 to 130 cm and an absolute error of 2.3 cm in the range of 20 to 90 cm for static testing and the IPS implemented in the selector bench obtained and absolute error of approximately 1.6 cm in the range of 22 to 55 cm. The system was able to select parts correctly in two of three predetermined areas and in the region that it did not worked properly there was little change in RSSI.